Family wisdom from the monk who sold his ferrari - "Sharma, Robin S" (Delhi, 2004)
This book is emphasized on the a simple yet strikingly effective system that shows you how to liberate that natural leadership potential of your child while creating a richer, more rewarding life for yourselfin the process.
Keywords: Family ethics